Conceptual Framework of Islamic Religious Education Curriculum Innovation in Primary Schools during the Era of the Industrial Revolution 4.0. - Abdullah Hasan Busri; Najwa Elfirdah; Ahmad Zakariya Al Anshori; Faqih Abdul Aziz; Ahmed Nur Hidayatullah Muhammad (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The Industrial Revolution 4.0 has fundamentally transformed the educational landscape, demanding systematic curriculum innovation, especially in Islamic Religious Education (PAI) at the primary school level. This study aims to develop a conceptual framework for innovating the PAI curriculum in primary schools within the context of the Industrial Revolution 4.0. Employing a systematic literature review methodology with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol, this research analyzed 20 articles published between 2015 and 2025, selected from an initial pool of 172 articles through a structured screening process. The synthesis reveals four key findings: (1) curriculum innovation in PAI must integrate the values of aqidah, syariah, and akhlak with digital literacy competencies; (2) the Tyler Rationale and Taba model provide complementary theoretical foundations for the design of PAI curriculum reform; (3) effective innovation requires a four-stage cyclical process of planning, organizing, implementation, and evaluation; and (4) the involvement of all stakeholders, educators, families, communities, and policymakers, is indispensable. Based on these findings, a conceptual framework is proposed in which digital literacy and Islamic values serve as dual inputs processed through the four stages of innovation to produce graduates who are spiritually grounded and digitally competent. These findings contribute to the body of knowledge on Islamic education reform in the digital era.